A new species of the New Zealand endemic weevil genus Clypeolus Broun (Coleoptera: Curculionidae: Cryptorhynchinae), found attacking an invasive weed, white horehound (Marrubium vulgare L. Lamiales: Lamiaceae) - Brown, Samuel D. J.; Leschen, Richard A. B.; Groenteman, Ronny (Zootaxa, 2025)
Clypeolus hallae Brown, Leschen and Groenteman new species is described from specimens reared from the roots of the invasive weed white horehound (Marrubium vulgare L., Lamiales: Lamiaceae) at a site in the Lowry Peaks Range, North Canterbury, in the South Island of New Zealand. Additional specimens from Kaitorete Spit, Kaikoura and Nelson in the South Island, Stephens Island and Wairarapa, Hawkes Bay and East Cape in the North Island have also been examined. We provide a synopsis of the genus Clypeolus Broun, and propose the following actions: Tychanus complexus Broun, 1921, Tychanus simulans Broun, 1921, Tychanus squamosus Broun, 1914, Tychanus terricola Broun, 1921, Acalles fuscidorsis Broun, 1909, and Acalles notoporhinus Broun, 1914 are new synonyms of Clypeolus cineraceus Broun, 1909; and Tychanus dux Broun, 1893 is a new synonym of Clypeolus lachrymosus (Broun, 1881). We include a key to the known species of Clypeolus, and images of the type specimens for available names, as well as diagnoses and the distribution for each species. Clypeolus hallae is an interesting example of an indigenous herbivore in a novel host association with an adventive invasive plant species, and we recommend further study into the biology and evolution of this weevil and its potential impacts upon horehound populations.